Host plants of Empria sawflies (Hymenoptera, Tenthredinidae) in Japan include Rhododendron (Ericaceae) - Shinohara, Akihiko; Hara, Hideho; Prous, Marko (Zootaxa, 2015)
New host plant records are given for six Empria species from Japan. They are Rosa multiflora [Rosaceae] for E. honshuana Prous & Heidemaa, 2011, Rubus sp. [Rosaceae] for E. japonica Heidemaa & Prous, 2011, Geum japonicum and G. calthifolium var. nipponicum [Rosaceae] for E. loktini Ermolenko, 1971, Rosa multiflora, Potentilla indica and probably Rubus parvifolius [Rosaceae] for E. quadrimaculata Takeuchi, 1952, Rhododendron molle subsp. japonicum [Ericaceae] for E. takeuchii Prous & Heidemaa, 2011, and Geum japonicum and Filipendula camtschatica [Rosaceae] for E. tridentis Lee & Ryu, 1996. This is the first record of Ericaceae as a host plant of Empria. The mode of host shifts in the evolution of Empria is inferred by using a phylogenetic hypothesis proposed by Prous et al. (2011a).